Contested Antiquity : Archaeological Heritage and Social Conflict in Modern Greece and Cyprus - Solomon, Esther; Anagnostopoulos, Aris; Bounia, Alexandra; Nikolaou, Paulina; Stylianou-Lambert, Theopisti; Galinki, Styliana; Gazi, Andromache; Konstantinou, Katerina; Mouliou, Marlen; Plantzos, Dimitris (New anthropologies of Europe., 2021)
How should visitors be introduced to an ancient Byzantine fortification that still holds the grim reminders of the cruel prison it was used as until the 1980s? How can foreign archaeological institutes engage with another nation's heritage in a meaningful way? What role do locals have in determining what is sacred, and can this sense of the sacred extend beyond buildings to the surrounding land? Together, the essays featured in Contested Antiquity offer fresh insights into the ways ancient heritage is negotiated for modern times.